2004
DOI: 10.1111/j.1572-0241.2004.30499.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Small Bowel Meal with Pneumocolon versus Ileo-Colonoscopy for the Diagnosis of Ileal Crohn's Disease

Abstract: Among 120 subjects, the reference standard TI diagnosis was normal in 47 (39.1%), lymphoid nodular hyperplasia (LNH) in 24 (20.0%), CD in 48 (40.0%), and NSAID enteropathy in 1 (0.9%). Colonoscopy provided TI images and/or biopsies in 97 cases (80.8%), while SBMP provided TI images in 119 (99.1%). When ileoscopy with biopsy succeeded, its accuracy was similar to SBMP with dual reading (89.7%vs 89.9%, p = NS) but superior to SBMP if interpreted only by the duty radiologist (80.0%, p < 0.05). Biopsy improved the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
0
15
0
4
Order By: Relevance
“…In a study by Marshall et al [13] , BMFTP was found to be as accurate as ileoscopy in diagnosing ter minal ileal disease. Minordi et al [14] showed that combining pneumocolon with BMFT improved the identification of terminal ileal and cecal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Marshall et al [13] , BMFTP was found to be as accurate as ileoscopy in diagnosing ter minal ileal disease. Minordi et al [14] showed that combining pneumocolon with BMFT improved the identification of terminal ileal and cecal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy with biopsy by a push endoscope is safe and useful procedure in selected patients with suggestive symptoms and failure of conventional radiology. Ileoscopy is superior for the diagnosis of CD of the terminal ileum when compared to small bowel radiology, whether performed as SBFT, enteroclysis or meal with pneumocolon [30] .…”
Section: Crohn's Disease (Cd)mentioning
confidence: 99%
“…Conventional endoscopic examinations used in the diagnosis of CD may not always provide enough data about the localization and the extension of the disease (1,2). As stated in the CD guidelines of ECCO (European Crohn's & Colitis Organization), the involvement area and the extension of the disease must be determined in order to plan an optional treatment (3).…”
Section: Introductionmentioning
confidence: 99%